Thermal properties of phase change material microcapsules modified coatings - Soh, Ernest Kee Ong. (2012)
The use of phase change materials (PCMs) for energy storage has received great attention in recent years and microencapsulation of phase change materials has been widely applied in various industries. Encapsulated phase change materials (PCMs) consist of an encapsulated core substance with a high latent heat of fusion. One of the possible applications of encapsulated phase change material is acting as a de-icing agent.